Influence of physical exercise on negative emotions in college students: chain mediating role of sleep quality and self-rated health - Mu, Fan-zheng; Liu, Jun; Lou, Hu; Zhu, Wei-dong; Wang, Zhen-cheng; Li, Bo (Frontiers in Public Health, 2024)
Background Negative emotions in college students are a significant factor affecting mental health, with suicide behaviors caused by negative emotions showing an annual increasing trend. Existing studies suggest that physical exercise is essential to alleviate negative feelings, yet the intrinsic mechanisms by which it affects negative emotions have not been fully revealed. Objective Negative emotions in college students represent a significant issue affecting mental health. This study investigates the relationship between physical exercise and negative emotions among college students, incorporating sleep quality and self-rated health (SRH) as mediators to analyze the pathway mechanism of how physical exercise affects students’ negative emotions. Methods A cross-sectional study design was utilized, employing online questionnaires for investigation. The scales included the Physical Activity Rating Scale-3 (PARS-3), the Depression Anxiety Stress Scales-21 (DASS-21), the Pittsburgh Sleep Quality Index (PSQI), and the 12-Item Short Form Health Survey (SF-12), resulting in the collection of 30,475 valid questionnaires, with a validity rate of 91%. Chain mediation tests and Bootstrap methods were applied for effect analysis. Results The proportions of university students engaged in low, medium, and high levels of physical exercise were 77.6, 13.1, and 9.3%, respectively. The proportions of students experiencing “very severe” levels of stress, anxiety, and depression were 4.5, 10.9, and 3.6%, respectively. Physical exercise was significantly positively correlated with self-rated health (r = 0.194, p < 0.01), significantly negatively correlated with sleep quality (r = −0.035, p < 0.01), and significantly negatively correlated with stress, anxiety, and depression (r = −0.03, p < 0.01; r = −0.058, p < 0.01; r = −0.055, p < 0.01). Sleep quality was significantly negatively correlated with self-rated health (r = −0.242, p < 0.01). Mediation effect testing indicated that sleep quality and self-rated health partially mediated the relationship between physical exercise and negative emotions, with total effect, total direct effect, and total indirect effect values of −1.702, −0.426, and − 1.277, respectively. Conclusion College students primarily engage in low-intensity physical activity. Sleep quality and self-rated health mediate the impact of physical exercise on students’ negative emotions. A certain level of physical activity can directly affect students’ emotional states and indirectly influence their negative emotions via sleep and self-rated health. Regular engagement in physical activities primarily positively impacts emotional states by enhancing mood stability and overall emotional resilience.